The impact of strabismus surgery on gait pattern in patients with congenital or starting within one year of age strabismus. (23rd March 2018) - Di Sipio, Enrica; Dickmann, Anna; Aprile, Irene; Germanotta, Marco; Simbolotti, Chiara; Salerni, Annabella; Savino, Gustavo; Padua, Luca
Highlights: Strabismus affects gait pattern. Our results showed that strabismus surgery influence gait differently depending on the time elapsed since surgery. These effects should be considered in tailored rehabilitation treatment. Abstract: Strabismus is a common visual disorder that negatively affects walking and balance. Therapeutic interventions for strabismus include strabismus surgery. Few studies investigated the relationship between strabismus surgery and postural control while, to the best of our knowledge, none has been conducted to assess the influence of strabismus surgery on gait. Therefore, the aim of this study was to evaluate the locomotion characteristics over patients with congenital or starting within one year of age strabismus, one month and three months after strabismus surgery. We enrolled 17 patients with a number of motor and sensorial features. Patients underwent an orthoptic and ophthalmological evaluation as well as a biomechanical evaluation before (T0) and after strabismus surgery (T1 at 1 month, and T2 at 3 months). We observed, mostly in T2 evaluation, significant improvements in the spatio-temporal parameters, such as cadence, velocity, swing, stance and double support phases, step and stride length. The kinematic results revealed a significant increase in hip ROM, strongly related to the improvement of gait speed. No significant differences has been observed in knee and ankle joint ROM. The kinetic results revealed a significant increase in the maximum moment at the knee and ankle joints associated with an increase in the maximum ankle power. Our findings suggest that the safety and balance control associated with gait improve in patients with strabismus following surgery.